Emotions and interactive tangible tools for math achievement in primary schools - Saccardo, Filippo; Decarli, Gisella; Missagia, Valentina Irene; Andrao, Margherita; Gini, Federica; Zancanaro, Massimo; Franchin, Laura (Frontiers in Psychology, 2024)
Acquiring mathematical concepts is crucial for students' academic achievements, future prospects and overall well-being. This study explores the role of emotions and the effectiveness of a tangible tool, SMARTER, in a symbolic number comparison task with a group of 59 students aged 6-7. The results show that using video clips to evoke positive emotions can improve task efficiency. Moreover, SMARTER enhances performance more effectively than traditional paper-and-pencil methods across various emotional states (neutral and positive emotions). These findings suggest that addressing emotional factors before engaging in a symbolic task can enhance learning and that interactive technology may give a more significant benefit to students with less positive attitudes toward the task.Incorporating effective teaching methodologies that utilize tangible devices within a positive emotional context can foster engagement and achievement in mathematics, optimizing students' learning experiences.